Tranformasi Sastra Lisan Krinok ke dalam Komposisi Musik Musik Orkestra - Gunawan, Indra; Handayani, Lusi; Irianto, Ikhsan Satria; Gustyawan, Tofan (Jurusan Sejarah, Seni, dan Arkeologi, FKIP Universitas Jambi, 2025)
Krinok oral literature can also be called performance literature because of its delivery by means of performance or show. In this article, it is discussed how the exploration of Krinok oral literature is transformed into a musical work or musical composition with an orchestral formation. The delivery style of Krinok oral literature with a singing style becomes the basis for the creation of the music itself such as singing text, tone, vocal melody, harmony, and development of structural forms. This music composition is titled “Bungo Bermada”, this title is made based on the meaning of praise. The method used is Mixed Method from qualitative and quantitative as the development of musical and extramusical ideas (philosophical aspects) into a musical composition “Bungo Bermada”,. The collection techniques consisted of interviews, observations, and literature studies. Meanwhile, the data analysis technique used consists of data reduction, data presentation, and conclusion drawing. For testing this product is a prototype of musical composition in the form of Digital Scoring (digital audio visual). Abstrak Sastra lisan Krinok dapat juga disebut sastra pertunjukan karena penyampaian nya dengan cara di pertunjukan atau dipertontonkan. Dalam artikel ini, dibahas bagaimana eksplorasi sastra lisa Krinok ditranspormasikan menjadi karya musik atau komposisi musik dengan formasi orkestra. Gaya penyampaian sastra lisan Krinok dengan gaya nyanyian menjadi dasar penciptaan musik itu sendiri seperti teks nyanyian, nada, melodi vokal, harmoni dan pengembangan bentuk struktur. Komposisi musik ini diberi judul “Bungo Bermada”, judul ini dibuat berdasarkan makna puji-pujian. Metode yang digunakan adalah Mixed Method dari kualitatif dan kuantitatif sebagai pengembangan gagasan musikal dan ekstramusikal (aspek filosofi) menjadi komposisi musik “Bungo Bermada”,. Teknik pengumpulan yang dilakukan terdiri dari wawancara, observasi dan studi pustaka. Sedangkan untuk teknik analisis data yang digunakan terdiri dari, reduksi data, penyajian data dan penarikan kesimpulan. Untuk pengujian produk ini adalah prototipe komposisi musik berupa Scoring Digital (audio visual digital).